Lenore Tawney : mirror of the universe. - Patterson, Karen (Karen E.); Tawney, Lenore; John Michael Kohler Arts Center (Chicago : The University of Chicago Press, 2019)
"Taking the course of Lenore Tawney's life as a starting point, this publication will function as an expanded biography. It will begin with her trajectory as an artist, weaving together important events, communities of artists, and individuals who made an impact on Tawney's artistic and spiritual practice."--Provided by publisher.
Foreword / Kathleen Mangan -- Introduction: mirror of the universe / Karen Patterson -- Impermanence 1907 to 1956 -- Student: 1945 to 1960 / Glenn Adamson -- The archive: ephemeral and eternal / Mary Savig -- Lost and proud, 1957 / Florica Zaharia -- Infrastructure 1907 to 1956 -- Sculptor: 1961 to 1970 / Glenn Adamson -- Mail art: the waters below the firmament / Mary Savig -- The bride, 1962 / Florica Zaharia -- Reflection 1907 to 1956 -- Seeker: 1970 to 1980 / Glenn Adamson -- Journals and correspondence: that point is the point / Mary Savig -- Dove, 1974 / Florica Zaharia -- Impact 1907 to 1956 -- Sage: 1980 to 2007 / Glenn Adamson -- Objects in the studio: this cage of bones, & blood, & flesh / Mary Savig -- Even thread has a speech / Shannon Stratton -- Written in water, 1979 / Florica Zaharia -- Afterword / Kathleen Mangan.
"This catalog is published on the occasion of Lenore Tawney: Mirror of the Universe, a series of four exhibitions exploring Lenore Tawney's life, work, and influence presented from August 18, 2019 to March 1, 2020 at the John Michael Kohler Arts Center."--Title page verso.
Edited by Karen Patterson.
boek
Keywords: Textile artists -- United States -- Biography; Women artists -- United States -- Biography; American Art -- 20th century -- Exhibitions; Textile crafts -- United States -- Exhibitions; Collage -- United States -- Exhibitions; Tawney, Lenore; Biographies; Exhibition catalogs